2016
DOI: 10.1002/prot.25214
|View full text |Cite
|
Sign up to set email alerts
|

Miz-1 and Max compete to engage c-Myc: implication for the mechanism of inhibition of c-Myc transcriptional activity by Miz-1

Abstract: c-Myc is a basic helix-loop-helix leucine zipper (b-HLH-LZ) transcription factor deregulated in the majority of human cancers. As a heterodimer with Max, another b-HLH-LZ transcription factor, deregulated and persistent c-Myc accumulates at transcriptionally active promoters and enhancers and amplifies transcription. This leads to the so-called transcriptional addiction of tumor cells. Recent studies have showed that c-Myc transcriptional activities can be reversed by its association with Miz-1, a POZ transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Recent research suggested that the transcriptional activities of c-Myc can be reversed once associated with Miz-1. Miz-1 competes with Max to form a complex with c-Myc through the b-HLH-LZ domain (between 12th and 13th zinc finger) ( Bédard et al, 2017 ). Miz-1 can interact with zinc-finger (ZF) transcriptional repressor growth factor independence 1 (Gfi-1) and Myc, form a ternary complex at the cyclin dependent kinase inhibitor (CDKN) promoter (including CDKN1A and CDKN2B), and repress CDKN synergistically ( Basu et al, 2009 ; Liu et al, 2010 ; Aesoy et al, 2014 ).…”
Section: Protein-protein Interaction Work On Myc Transcriptional Repressionmentioning
confidence: 99%
“…Recent research suggested that the transcriptional activities of c-Myc can be reversed once associated with Miz-1. Miz-1 competes with Max to form a complex with c-Myc through the b-HLH-LZ domain (between 12th and 13th zinc finger) ( Bédard et al, 2017 ). Miz-1 can interact with zinc-finger (ZF) transcriptional repressor growth factor independence 1 (Gfi-1) and Myc, form a ternary complex at the cyclin dependent kinase inhibitor (CDKN) promoter (including CDKN1A and CDKN2B), and repress CDKN synergistically ( Basu et al, 2009 ; Liu et al, 2010 ; Aesoy et al, 2014 ).…”
Section: Protein-protein Interaction Work On Myc Transcriptional Repressionmentioning
confidence: 99%
“… 115 , 117 Due to the profound functional implication of the MYC/MIZ1 interaction on MYC activity, fostering this association via small molecule inhibition of HUWE1 has been explored as a therapy. 113 , 115 , 116 , 118 , 119 The small compounds BI8622 and BI8626 are specific inhibitors of HUWE1 that enhance MYC proteolysis and suppress MYC-dependent transactivation resulting in inhibition of cell growth in colon carcinoma and multiple myeloma. 116 , 120 In vivo , HUWE1 knock-down clearly reduces tumor burden, but both BI8622 and BI8626 have suboptimal pharmacokinetics that prevents the assessment of their in vivo efficacy in MYC-driven tumor models.…”
Section: Targeting Mycmentioning
confidence: 99%
“…The canonical role of MYC is to act as a transcriptional regulator in a dimeric DNA-binding complex with MAX [ 20 ]. Although MYC-MAX dimers generally stimulate transcription, MYC can also repress target genes via association with the zinc-finger transcription factor Miz-1 [ 21 ]. While the number of transcriptionally activated target genes of MYC is substantial, many transcriptionally repressed targets have also been identified.…”
Section: Discussionmentioning
confidence: 99%